Об одной задаче преследования при интегрально-геометрических ограничениях - Игнатенко, А.П. (Теорія оптимальних рішень, 2007)
This paper deals with differential pursuit game under geometric and integral constraints on controls. There is constructed resolving function of system and found game ending conditions.